Sexing the body: Gender politics and the construction of sexuality - Fausto-Sterling, Anne (Basic Books, 2000)
Discusses the causes and determining factors of gender behavior differences and sexual identity, particularly biology and societal expectations, and argues that differences between male and female are not always distinct.
Keywords: approches et analyses; corps; cours; discipline; discours dominant; féminisme matérialiste; genre; histoire et politique; hétérosexisme; injustices épistémiques; philosophie politique; premier cycle; production des savoirs; ressource en ligne; sciences humaines; sciences sociales; sex3383; sexe/genre; sexualité; sociologie; systèmes d'oppressions; thématiques; épistémologie

Carnal appetites: food, sex, identities - Probyn, Elspeth (Routledge, 2000)
n Carnal Appetites, Elspeth Probyn charts the explosion of interest in food - from the cults that spring up around celebrity chefs, to our love/hate relationship with fast food, our fetishization of food and sex, and the impact of our modes of consumption on our identities. 'You are what you eat' the saying goes, but is the tenet truer than ever? As the range of food options proliferates in the West, our food choices become inextricably linked with our lives and lifestyles. Probyn also tackles issues that trouble society, asking questions about the nature of appetite, desire, greed and pleasure, and shedding light on subjects including: fast food, vegetarianism, food sex, cannibalism, forced feeding, and fat politics.
Keywords: approches et analyses; care; corps; cours; discipline; féminisme pop; lit4700; premier cycle; ressource en ligne; sciences humaines; sciences sociales; sexualité; thématiques; études de genres